Advances in myopia prevention strategies for school-aged children: a comprehensive review - Tariq, Farheen; Mobeen, Rabia; Wang, Xinhai; Lin, Xiao; Bao, Qingdong; Liu, Jinhui; Gao, Hua (Frontiers in Public Health, 2023)
Myopia has significantly risen in East and Southeast Asia, and the pathological outcomes of this condition, such as myopic maculopathy and optic neuropathy linked to high myopia, have emerged as leading causes of irreversible vision loss. Addressing this issue requires strategies to reduce myopia prevalence and prevent progression to high myopia. Encouraging outdoor activities for schoolchildren and reducing near-work and screen time can effectively prevent myopia development, offering a safe intervention that promotes healthier habits. Several clinical approaches can be employed to decelerate myopia progression, such as administering low-dose atropine eye drops (0.05%), utilizing orthokeratology lenses, implementing soft contact lenses equipped with myopia control features, and incorporating spectacle lenses with aspherical lenslets. When choosing an appropriate strategy, factors such as age, ethnicity, and the rate of myopia progression should be considered. However, some treatments may encounter obstacles such as adverse side effects, high costs, complex procedures, or limited effectiveness. Presently, low-dose atropine (0.05%), soft contact lenses with myopia control features, and orthokeratology lenses appear as promising options for managing myopia. The measures mentioned above are not necessarily mutually exclusive, and researchers are increasingly exploring their combined effects. By advocating for a personalized approach based on individual risk factors and the unique needs of each child, this review aims to contribute to the development of targeted and effective myopia prevention strategies, thereby minimizing the impact of myopia and its related complications among school-aged children in affected regions.